2018
DOI: 10.1088/1751-8121/aad57b
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of exploding phase spaces: ontic open systems

Abstract: The volume of phase space may grow super-exponentially ("explosively") with the number of degrees of freedom for certain types of complex systems such as those encountered in biology and neuroscience, where components interact and create new emergent states. Standard ensemble theory can break down as we demonstrate in a simple model reminiscent of complex systems where new collective states emerge. We present an axiomatically defined entropy and argue that it is extensive in the micro-canonical, equal probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…, see [11]. In this paper we show that it is indeed possible to find a complete classification of complex stochastic systems, including the super-exponential case.…”
Section: ( )mentioning
confidence: 66%
See 2 more Smart Citations
“…, see [11]. In this paper we show that it is indeed possible to find a complete classification of complex stochastic systems, including the super-exponential case.…”
Section: ( )mentioning
confidence: 66%
“…These coins are magnetic, so that any two can stick to each other to create a pair which is a third state obtained by interactions of elements (one possible configuration). As mentioned before, in [11] it is shown that the phasespace volume can be obtained recursively…”
Section: Super-exponential Growth: Magnetic Coinsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, the results are applied for the derivation of maximum entropy distributions and thermostatistical relationships for supra-extensive entropy [21], which have not been considered so far. Presented framework could also be applied for thermostatistical analysis of another SPA entropies not considered here, such as Bekenstein-Hawking entropy [32] and superexponential entropy [33], as well as for more general group entropies [34], [22] [35], [36], [37], [38]. The framework can particularly be useful for the analysis of thermodynamic stability of SPA entropies [18], [16] which will be discussed elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the sample space grows sub-exponentially, W ARW ∼ 2 √ N /2 , and S ARW = (log W ARW ) 2 . The next example is the magnetic coin model (MC) [21], where each coin can be in two states: head or tail, however, two coins can also stick together and create a bond state. It can be shown that the corresponding sample space grows super-exponentially, W M C ∼ N N/2 e 2 √ N .…”
Section: Scaling Expansion Of the Volume Of Configuration Spacementioning
confidence: 99%